Himalayan wolf foraging ecology and the importance of wild prey - Geraldine Werhahn; Naresh Kusi; Xiaoyu Li; Cheng Chen; Lu Zhi; Raquel Lázaro Martín; Claudio Sillero-Zubiri; David W. Macdonald (Global Ecology and Conservation, 2019)
Carnivore predation on livestock and game species leads to human-carnivore conflict. Thus, understanding the foraging ecology of threatened carnivores is important for conservation planning. We explore the summer diet of the Himalayan wolf, and of sympatric carnivores, based on the analysis of 257 field collected and genetically confirmed scat samples collected across three study areas in the Himalayas of Nepal (Humla, Dolpa, and Kanchenjunga Conservation Area) and two study areas on the Tibetan Plateau of China (Zhaqing and Namsai Township). We compared the prey species consumed to the relative availability of wild and domestic prey species. Himalayan wolves tend to select wild over domestic prey, smaller (e.g. Tibetan gazelle, Procapra picticaudata) over larger sized wild ungulates (e.g. White-lipped deer, Cervus albirostris), and plains-dwelling (Tibetan gazelle) over cliff-dwelling ungulates (naur, Pseudois nayaur). Tibetan gazelle was consistently selected for by the Himalayan wolf and smaller mammals such as Himalayan marmot (Marmota himalayana), woolly hare (Lepus oiostolus) and pikas (Ochotona spp.) are important supplementary food resources. Himalayan wolves avoided livestock which showed a seasonal high abundance, that exceeded many-fold the abundance of wild prey species during the summer study period. Given this seasonally high livestock abundance, depredation by Himalayan wolves is inevitable and a major conservation concern. Habitat encroachment and depletion of wild prey populations are important drivers of this conflict. But we found that livestock was avoided when wild prey was available, a finding that can direct conservation. We conclude that the protection of Himalayan wolves, and other sympatric carnivores can be enhanced by a) securing healthy wild prey populations (ungulates and small mammals) through setting aside wildlife habitat refuges, and b) more sustainable livestock herding including reduced livestock loads and improved herding practices and protection. Keywords: Canis lupus chanco, Conservation, Depredation conflict, Foraging ecology, Himalayan wolf, Wolf diet